2014
DOI: 10.3846/16486897.2013.804828
|View full text |Cite
|
Sign up to set email alerts
|

Bioindication of Trace Metal Pollution in the Atmosphere of Baku City Using Ligustrum Japonicum, Olea Europea, and Pyracantha Coccinea Leaves

Abstract: Abstract. Trinitrotoluene (TNT), a commonly used explosive for military and industrial applications, can cause serious environmental pollution. 28-day laboratory pot experiment was carried out applying bioaugmentation using laboratory selected bacterial strains as inoculum, biostimulation with molasses and cabbage leaf extract, and phytoremediation using rye and blue fenugreek to study the effect of these treatments on TNT removal and changes in soil microbial community responsible for contaminant degradation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The reason for the formation of necrosis is photodynamic and free radical oxidation as well as chemical poisoning of cells by high concentrations of toxic compounds. It has been shown that plants can accumulate heavy metals in their leaves, in particular lead (Youssef et al, 2014). In gas mixtures nitrogen oxides synergistically enhance the phyto-toxicity of sulfur oxide (IV).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the formation of necrosis is photodynamic and free radical oxidation as well as chemical poisoning of cells by high concentrations of toxic compounds. It has been shown that plants can accumulate heavy metals in their leaves, in particular lead (Youssef et al, 2014). In gas mixtures nitrogen oxides synergistically enhance the phyto-toxicity of sulfur oxide (IV).…”
Section: Discussionmentioning
confidence: 99%
“…BioMAP itself deals already more than 20 years with these innovative methods (some relevant examples on B&B activities are given in Almeida et al 2015;Branquinho et al 2008;Chudzińska et al 2015;El-Khabib et al 2011;Figueiredo et al 2001;Freitas et al 2007;Frontasyeva et al 2004 andGorelova et al 2010, Kang et al 2008Lodenius et al 2005, Loppi et al 1994Loppi and Bonini 2000;Nassri et al 2015;Markert et al 2014 andPaoli et al 2013;Prapamontol et al 2014;Saiki et al 2007;Samson et al 2015;Steinnes et al 1997 andSuchara et al 2011;Vuković et al 2015;Youssef et al 2014;Wolterbeek et al 1995 andWünschmann et al 2008). Yet, there is another realm of science where the accreditation and quality control measures have a long and formally well-understood tradition: analytical chemistry.…”
Section: Methods Of Quality Control In B and B Technologies And Analytimentioning
confidence: 97%
“…This method is very advantageous since the cost is low and it can be used on a large scale with high efficiency, offering an interesting tool to monitor heavy metal contamination in the air and soils (Pirintsos and Loppi 2008;Stamenkovic et al 2013;Antonucci et al 2016;Belguidoum et al 2020). Several higher plants have been used to assess metal contamination in the air and soils because of their accumulation properties (Al-Khlaifat and Al-Khashman 2007;Berlizov et al 2007;Di Lonardo et al 2011;Youssef et al 2014, Belguidoum et al 2020Vannucchi et al 2020). Studies have shown that the leaves of higher plants adsorb MTE from wet and dry atmospheric deposition and accumulate metals from the soil and the atmosphere (Maher et al 2008;Barış et al 2015;Lograda et al 2016).…”
Section: Introductionmentioning
confidence: 99%